Integrated Maintenance Management to Increase the Availability of Drilling Equipment: Case Study in a Peruvian Mine - Banda, Lourdes (2024)
Drilling equipment is the main asset of mining companies; therefore, a decrease in the operability and availability of such equipment can generate negative impacts on organizations, such as the generation of extra expenses due to the hiring of third parties for the performance of activities and contractual projects. According to statistics from previous studies, the availability of equipment in the sector should be 95% to be considered optimal for use in mining operations. Equipment downtime can be avoided by establishing and following a preventive maintenance schedule and having spare parts and hydraulic components readily available for maintenance. The purpose of this work is the implementation and follow-up of a maintenance management plan based on a failure mode analysis and autonomous maintenance and preventive maintenance with the purpose of keeping the equipment in optimal conditions, maintaining an adequate level of availability and extending the useful life of the assets. With the simulation of the Arena program, a possible availability of 95% was evidenced, which corresponds to being adequate for the optimal operation of the equipment and the continuity of the projects.